2013
DOI: 10.3109/09546634.2012.739679
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intradermal injection with iontophoresis of abobotulinum toxin A for the treatment of primary axillary hyperhidrosis: A randomized, controlled trial

Abstract: This study has shown that injection is a more effective method for the administration of BTX-A, though iontophoresis can also be considered a non-invasive and painless method in some patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Duration of effect is only a few days with tap water and anticholinergic iontophoresis [19], however iontophoresis with BoNT may provide relief for three months [24]. Out of 27 patients who underwent iontophoresis with BoNT, 100% were found to have statistically significant improvement in sweating via gravimetry ( p < 0.05) [24,25,26]. The short- lived effect of current methods of electrophoresis makes it undesirable [27].…”
Section: Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Duration of effect is only a few days with tap water and anticholinergic iontophoresis [19], however iontophoresis with BoNT may provide relief for three months [24]. Out of 27 patients who underwent iontophoresis with BoNT, 100% were found to have statistically significant improvement in sweating via gravimetry ( p < 0.05) [24,25,26]. The short- lived effect of current methods of electrophoresis makes it undesirable [27].…”
Section: Treatmentsmentioning
confidence: 99%
“…In a prospective, assessor blind study, Montaser-Kouhsari et al [25] compared the effect of A/Abo injection with A/Abo iontophoresis in 11 patients with AH. A/Abo (250 U) was injected intradermally into one axilla and the same dose was iontophoresed in the other.…”
Section: Axillary Hyperhidrosis (Ah)mentioning
confidence: 99%
See 1 more Smart Citation
“…A preliminary randomized study comparing iontophoretically administered vs . intradermal injections of botulinum toxin treatment in patients with palmar hyperhidrosis recently showed that injections are more effective but more painful for the administration of BTX‐A . A larger trial is currently ongoing (clinicaltrials.gov identifier: NCT01262339) and will provide further data.…”
Section: Current Applications and Perspectivesmentioning
confidence: 99%
“…They have revealed the superiority of botulinum treatment in all measured points (respectively 84%, 76% and 50% vs 73%, 22%, and 32%). Short observation period may be considered to be disadvantage of their research (44).…”
Section: Botulinum Toxin Therapymentioning
confidence: 99%